2018
DOI: 10.7556/jaoa.2018.100
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Training in Osteopathic Medical Schools: Results of a National Survey

Abstract: Oral health education is present at many osteopathic medical schools, but the content covered and the extent of training varies considerably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(31 reference statements)
0
8
0
1
Order By: Relevance
“…[20][21][22] In the current study, we planned to conduct two or three interviews per discipline (for a total of 26 to 39 interviews) from the survey respondents who expressed a willingness to have a longer conversation about oral health education in their primary care training program. [20][21][22] In the current study, we planned to conduct two or three interviews per discipline (for a total of 26 to 39 interviews) from the survey respondents who expressed a willingness to have a longer conversation about oral health education in their primary care training program.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22] In the current study, we planned to conduct two or three interviews per discipline (for a total of 26 to 39 interviews) from the survey respondents who expressed a willingness to have a longer conversation about oral health education in their primary care training program. [20][21][22] In the current study, we planned to conduct two or three interviews per discipline (for a total of 26 to 39 interviews) from the survey respondents who expressed a willingness to have a longer conversation about oral health education in their primary care training program.…”
Section: Methodsmentioning
confidence: 99%
“…13 In 2005, the Society of Teachers of Family Medicine Group on Oral Health published its oral health curriculum, Smiles for Life, which has evolved into a multi-professional resource. [20][21][22] Those surveys found that some disciplines had made signiicant progress in integrating oral health into primary care training, while others lagged behind. 15 New York University's College of Nursing developed the Oral Health Nursing Education and Practice initiative to encourage oral health training in nursing 16 and to replace the traditional HEENT (head, ears, eyes, nose, and throat) examination with the HEENOT (adding to this exam: teeth, gums, mucosa, tongue, and palate) to address oral-systemic health issues.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Center for Integration of Primary Care and Oral Health (CIPCOH), a national center based at Harvard University and funded by the Health Resources and Services Administration, surveyed 14 primary care specialties ranging from nursing to pediatrics to family medicine to pharmacy about their oral health curricula and learning objectives. [8][9][10][11][12][13][14] Although a majority of survey respondents agreed that oral health knowledge is important for their learners, most reported that their curricula includes only 1-3 hours of oral health instruction. [8][9][10][11][12][13][14] Given the close association of poor oral health and its attendant inflammation with cardiovascular disease, diabetes, and other noncommunicable diseases, this is not enough.…”
Section: The Problemmentioning
confidence: 99%